Labour Lines and Colonial Power : Indigenous and Pacific Islander Labour Mobility in Australia. - Stead, Victoria (Aboriginal History Monographs., 2019)
"Today, increases of so-called 'low-skilled' and temporary labour migrations of Pacific Islanders to Australia occur alongside calls for Indigenous people to 'orbit' from remote communities in search of employment opportunities. These trends reflect the persistent neoliberalism within contemporary Australia, as well as the effects of structural dynamics within the global agriculture and resource extractive industries. They also unfold within the context of long and troubled histories of Australian colonialism, and of complexes of race, labour and mobility that reverberate through that history and into the present. The contemporary labour of Pacific Islanders in the horticultural industry has sinister historical echoes in the 'blackbirding' of South Sea Islanders to work on sugar plantations in New South Wales and Queensland in the late nineteenth and early twentieth centuries, as well as in wider patterns of labour, trade and colonisation across the Pacific region. The antecedents of contemporary Indigenous labour mobility, meanwhile, include forms of unwaged and highly exploitative labouring on government settlements, missions, pastoral stations and in the pearling industry. For both Pacific Islanders and Indigenous people, though, labour mobilities past and present also include agentive and purposeful migrations, reflective of rich cultures and histories of mobility, as well as of forces that compel both movement and immobility. Drawing together historians, anthropologists, sociologists and geographers, this book critically explores experiences of labour mobility by Indigenous peoples and Pacific Islanders, including Māori, within Australia. Locating these new expressions of labour mobility within historical patterns of movement, contributors interrogate the contours and continuities of Australian coloniality in its diverse and interconnected expressions. "